Dog vs. Strawberry - Buchet, Nelly (Random House Studio, an imprint of Random House Children's Books, 2024)
When Dog is handed a strawberry from the fruit bowl, she sizes it up, dances around it, and decides she is going to race the Strawberry--and win.